Mitigating the impact of COVID-19 on colorectal cancer screening: Organized service screening perspectives from the Asia-Pacific region - Chiu, Han-Mo; Su, Chiu-Wen; Hsu, Weng-Feng; Jen, Grace Hsiao-Hsuan; Hsu, Chen-Yang; Chen, Sam Li-Sheng; Chen, Hsiu-Hsi (Preventive medicine, 2021)
Colorectal cancer(CRC) is one of the most prevalent malignancies in the Asia-Pacific region, and many countries in this region have launched population CRC service screening. In this study, CRC screening key indicators, including the FIT(fecal immunochemical test) screening rate (or participation rate) and the rate of undergoing colonoscopy after positive FIT in 2019 and 2020, were surveyed in individual countries in the Asia-Pacific region. The impact of the pandemic on the effectiveness of CRC screening was simulated given different screening rates and colonoscopy rates and assuming the pandemic would persist or remain poorly controlled for a long period of time, using the empirical data from the Taiwanese program and the CRC natural history model. During the COVID-19 pandemic, most of the programs in this region were affected, but to different extents, which was largely influenced by the severity of the local pandemic. Most of the programs continued screening services in 2020, although a temporary pause occurred in some countries. The modeling study revealed that prolonged pauses of screening led to 6% lower effectiveness in reducing CRC mortality. Screening organizers should coordinate with health authorities to elaborate on addressing screening backlogs, setting priorities for screening, and applying modern technologies to overcome potential obstacles. Many novel approaches that were developed and applied during the COVID-19 pandemic, such as the risk-stratified approach that takes into account personal CRC risk and the local epidemic status, as well as new digital technologies, are expected to play important roles in CRC screening in the future. •More than half of global colorectal cancers (CRCs) currently occur in the Asia-Pacific region.•The COVID-19 pandemic has significantly affected CRC screening service globally, but less so in the Asia-Pacific region.•Risk-stratified approach and modern technologies are the key to mitigating the impact of pandemics on CRC screening.